(untitled) (Archive of Conferences, 2020)
In the current public health crisis, we are all working quickly to move our classes out of the classroom. Fortunately, even if online teaching and learning are new to us, there is a lot of experience to draw on. On this article have been compiled the best resources, learning activities, and other aspects of online instruction.